Enhancing Iraqi efl undergraduate learners' perception and production of intonation via an interactive training approach - Barih, Hayder Kubashi (2021)
Intonation is considered not only more important than grammar but also as the decisive component of better communicative skills. Teaching intonation has been one of the most neglected areas in English language teaching at different level in Iraq. Therefore, this study has attempted to identify the difficulties that Iraqi EFL students face in learning intonation systems; namely tonality, tonicity, and tones. The study also examined the perceptions of the students towards the use of intonation learning strategies. Moreover, the study examined the ways intonation learning strategies used by Iraqi EFL learners facilitated in enhancing their awareness and production of intonation systems. Lastly, the study sought to assess the significance of the intonation training course in enhancing the mastery of Iraqi EFL learners’ use of intonation. The study employed a research design which involved gathering qualitative and quantitative data sequentially. Specifically, two main methods were used to collect the data: diary reports and intonation perception and production tests, as well as interviews and field notes. The findings of the study indicated that the Iraqi EFL students faced some difficulties related to learning condition, personal difficulties, language use and the Arabic influence. Findings of the study showed varied use of intonation learning strategies by the students, ranging from general learning strategies such as pair and group work, solving learning problem to more specific ones, such as reflections towards listening strategies, reflections towards presentation strategies, imitation strategies, intonation analysis, and getting feedback on and sharing information about intonation. The findings also indicate that there is an effect of the English intonation training on the enhancement of the undergraduate students' intonation production. The study suggests the need to include the systems of English intonation in Iraqi EFL undergraduate classes to help enhance the correct use of intonation in speech.